1998
DOI: 10.1212/wnl.50.5.1323
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine as treatment for dyskinesias and motor fluctuations in Parkinson's disease

Abstract: These findings suggest that amantadine given as adjuvant to levodopa can markedly improve motor response complications and support the view that hyperfunction of NMDA receptors contributes to the pathogenesis of levodopa-associated motor complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
2
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(86 citation statements)
references
References 7 publications
3
76
2
2
Order By: Relevance
“…A numerical reduction in OFF time, a secondary endpoint, suggested possible improvement in underlying PD symptoms. Previous studies have reported improvement in motor fluctuations4 with amantadine, but the improvement in OFF time seen in our study did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A numerical reduction in OFF time, a secondary endpoint, suggested possible improvement in underlying PD symptoms. Previous studies have reported improvement in motor fluctuations4 with amantadine, but the improvement in OFF time seen in our study did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 99%
“…More recently, amantadine was reported to improve levodopa‐induced dyskinesia (LID) 4, 5, 6, 7. The clinical use of amantadine is limited because of tolerability issues, although doses up to a maximum of 400 mg/d, in divided doses, are approved for use in PD.…”
mentioning
confidence: 99%
“…Interestingly, the NMDA receptor antagonist amantadine suppresses the expression of levodopainduced dyskinesias [29] and was also found to be effective in reducing punding in a PD patient [30]. Moreover, punding is associated with ICDs, according to a recent cross-sectional study [31].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, cortically induced NMDA activation would not match the sustained activation from experimental bath application of NMDA, and these more physiological mechanisms remain to be explored computationally. Interestingly, the administration of various NMDA antagonists, such as amantadine and memantine, yields improvements in motor signs in Parkinson's disease patients (Blandini et al 2001;Metman et al 1998;Varanese et al 2010). Experiments have also been done to investigate how particular NMDA antagonists affect NMDA currents in parkinsonian conditions.…”
Section: Discussionmentioning
confidence: 99%